Math City Map: Application of Mathematics Outdoor Learning Using Mobile Application - Wulandari, Tri Candra; Raicucu, M. Indra Riamizad; Abidin, Zainal; Fajarianto, Otto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The purpose of this research is to describe the design of outdoor learning using Math City Map (MCM) application. Through several features provided in Math City Map teachers can provide a virtual classroom that serves to support, hone and explore student abilities. This outdoor learning design is the result of the development of learning design in mathematics subjects in elementary and secondary schools. This research uses a qualitative approach, with a descriptive research type. The subjects of this research were teachers and students in Singosari. Data collection techniques using documentation, interviews and observation. The results of the learning design using MCM through four stages, there are 1) determining the learning theme, and outdoor destination or location, 2) briefing all related parties, namely students, teachers and assistants, 3) dividing students into groups, 4) implementing outdoor learning. Implementation of outdoor learning.